Rural Malawi households' environmental concern and consciousness about appropriate energy consumption practices amidst prevailing socio-economic conditions - Erasmus, Alet C. (Aletta Catharina) (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.